On the taxonomy of the genus Lethe Hübner (Lepidoptera, Papilionoidea, Nymphalidae, Satyrinae) with description of a new species - Huang, Si-Yao; Lang, Song-Yun; Müller, Günter C. (Zootaxa, 2024)
New information on the genus Lethe is presented. A new species of the Lethe tristigmata-complex, L. sunglam sp. nov. is described from Mt. Fansipan, northern Vietnam. The individual variation of Lethe jianqingi Lang, 2016 is discussed and its female is reported for the first time and compared with the related taxa. Lethe lyncus de Nicéville, 1897 is found to be a good species different from the related congeners, and L. wui H. Huang, 1999 was synonymized with it (syn. nov.). Adults and male genitalia of the aforementioned taxa and related ones as well are illustrated.